2015
DOI: 10.5194/bg-12-3009-2015
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal dynamics of organic carbon and metals in thermokarst lakes from the discontinuous permafrost zone of western Siberia

Abstract: Abstract. Despite relatively good knowledge of the biogeochemistry of Siberian thermokarst lakes during summer base flow, their seasonal dynamics remains almost unexplored. This work describes the chemical composition of ~130 thermokarst lakes ranging in size from a few m2 to several km2, located in the discontinuous permafrost zone. Lakes were sampled during spring flood, just after the ice break (early June), the end of summer (August), the beginning of ice formation (October) and during the full freezing se… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
84
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 86 publications
(91 citation statements)
references
References 45 publications
6
84
1
Order By: Relevance
“…4a). These values of SUVA 280 are consistent with those of the lakes (2 to 4 L mg −1 m −1 ; Manasypov et al, 2015) and rivers (2 to 3.5 L mg −1 m −1 ; Pokrovsky et al, 2015) of the region during summer period. The previously published values of SUVA 280 in WSL surface waters were similar across a large scale of lake size (from 50 to 500 000 m 2 ) and latitudinal position of the river watershed (from 57 to 66 • N).…”
Section: Dissolved Organic Carbon Transport In Peat Soilssupporting
confidence: 84%
See 1 more Smart Citation
“…4a). These values of SUVA 280 are consistent with those of the lakes (2 to 4 L mg −1 m −1 ; Manasypov et al, 2015) and rivers (2 to 3.5 L mg −1 m −1 ; Pokrovsky et al, 2015) of the region during summer period. The previously published values of SUVA 280 in WSL surface waters were similar across a large scale of lake size (from 50 to 500 000 m 2 ) and latitudinal position of the river watershed (from 57 to 66 • N).…”
Section: Dissolved Organic Carbon Transport In Peat Soilssupporting
confidence: 84%
“…The specific UV absorbency (SUVA 280 , L mg −1 m −1 ) is used as a proxy for aromatic C, molecular weight, and source of dissolved organic matter (DOM) (Uyguner and Bekbolet, 2005;Weishaar et al, 2003;Ilina et al, 2014, and references therein). The SUVA 280 in the present study was used for consistency with previous measurements of lakes and rivers in western Siberia (Shirokova et al, 2013;Manasypov et al, 2015Manasypov et al, , 2017Pokrovsky et al, 2015) and permafrost-draining rivers in central Siberia .…”
Section: Analysesmentioning
confidence: 99%
“…To identify the group of elements that behaved in a similar way in snow water and snow particles, we applied a complementary hierarchical cluster analysis (HCA; Hartigan, 1975;Kaufman and Rousseeuw, 2005), which is widely adopted in geochemical interpretations of element concentration data (e.g., Bini et al, 2011;Levitan et al, 2015;Schot and van der Wal, 1992;Moragues-Quiroga et al, 2017). We used Ward's method (Ward, 1963) for the linkages rule, following previous studies (Gourdol et al, 2013;Lin et al, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…It has also been shown that CDOM values in the lakes of the Lena River Delta are lower than those in Central Yamal lakes [53]. Lake catchments in Abnizova et al and Manasypov et al [57,58] are small and therefore relatively low influenced by snow melt in spring and are not characterized by large coverage of dense shrub biomass that is abundant in the Central Yamal. Lakes in the boreal biome show higher CDOM than the Arctic biome.…”
Section: Organic Matter Content In Arctic Lakesmentioning
confidence: 98%
“…Abnizova et al and Manasypov et al [57,58] investigated DOC in lake-rich tundra landscapes in the Lena River Delta and Western Siberia. Both studies found lower DOC values than what we found for the lakes in the Central Yamal (unpublished data).…”
Section: Organic Matter Content In Arctic Lakesmentioning
confidence: 99%